Components of the yield and bromatological composition of three Brachiaria varieties in El Empalme area, Ecuador - Reyes-Pérez, J. J.; Méndez-Martínez, Y.; Verdecia, D. M.; Luna-Murillo, R. A.; Hernandez-Montiel, L. G.; Herrera, R. S. (Cuban Journal of Agricultural Science, 2018)
Using a random block design with factorial arrangement (3x3) with five replications, the components of the yield and bromatological composition of three Brachiaria varieties (Decumbens, Brizantha and Mulato l) and three regrowth ages (21, 42 and 63 days) were studied in El Empalme area, Ecuador. The yields of total dry matter, biomass, leaves and stems were determined, as well as the plant height, length and width of leaves, the contents of DM, CP, NDF, ADF, ADL, cellulose (Cel), hemicellulose ( Hcel), cellular content (CC), P, Ca, ash, OM, DMD, OMD, ME, FNE and relations leaf-stem, NDF-N and ADF-N. Analysis of variance was performed according to experimental design. There was significant interaction (P<0.0001) between the varieties and the regrowth age for all the studied indicators. The highest DM and biomass yields were obtained in Mulato 1 at 63 days of regrowth (2.49 and 8.64 t/ha, respectively). The CP and CC decreased with the maturity of the plant and the best values were obtained in Mulato 1 and Brizantha at 21 days of regrowth (14.23 and 74.77 %, respectively), while the components of the cell wall increased with age and Decumbens showed the highest values. There was variability in the studied indicators in the varieties, with the best general performance for Mulato 1. It was demonstrated that as the maturity of the plant advanced, there was a decrease in its nutritional quality, determined among other aspects, by the lower digestibilities and energy, as well as increases in the relations NDF/N, ADF/N. However, although leaf/stem ratio decreased with age, leaf production in all studied cultivars was above 50 % with respect to stems, aspects to be taken into account in the management of these plants in ruminants production systems. Key words: bromatological composition, regrowth age, Brachiaria, quality, digestibility, energy